Police culture: An empirical appraisal of the phenomenon - Demirkol, Ismail Cenk (Criminology & criminal justice, 2020)
Although police culture is a widely researched topic, not much is known about the nature of the relationships among the various components and the degree to which they are critical in the make-up of police culture. In this study, we revisit the concept of police culture and explore the nature and directions of the relationships among the various elements that constitute police culture. Drawing data from a survey of 1970 Turkish National police officers we identify six commonly recognized dimensions of police culture based on the existing literature. The results from the four different confirmatory factor analyses (CFA) indicate that of the six dimensions, the first-order CFA with five factors best fit the data. Further, the results suggest that police culture did not account for the covariation among the six first-order factors. These findings suggest that police culture is a more complex and multifaceted concept than the prior literature suggests.